Errors Made by the Second Semester Students of the English Department at Widya Mandala Catholic University Surabaya in Learning English Tenses as Reflected in Their Narrative Writing - Ervina Hartono (Magister Scientiae, 2008)
People realize that writing cannot be separated from their lives such as in the school and college, they have to make essays or journals for their subjects and in the office, they have to make business letters or reports for their job. Realizing that writing is very important, the writer did an error analysis on the students’ tenses in their narrative writing. The reasons why the writer conducted this research are to find out to what extend the second semester students of the English Department at WMCUS acquire the English tenses as reflected in their narrative writing, to find out the possible sources of errors that the student make in constructing English tenses in their narrative composition, and to suggest the possible solutions of the problems. The subjects are the second semester students of Widya Mandala Catholic University Surabaya. The writer took two classes: class B and C. The writer took the two class in the middle of the six classes. The writer collected the students’ test papers which were the data before they are marked by the lecturers. Then, the writer analyzed the data by recognizing and identifying errors, counting the frequency of error occurrences, classifying the identified errors according to the source of errors, interpreting the findings, making conclusion and suggestions. In analyzing the data, the writer did not use one of the Larry Selinker’s sources of error―Transfer of Training is not included because the source can be seen in Speaking clearly. The writer did not use the Transfer of Training to analyze the sources of errors in the data analysis. The results of the analysis are as follows: The sources of errors that contribute are Language Transfer (7% errors), Strategies of Second Language Learning (54,3% errors), Strategies of Second Language Communication (1,6% errors), and Overgeneralization of Target Language Material (37,1% errors). The prominent errors are Strategies of Second Language Learning (54,3% errors) and Overgeneralization of Target Language Material (37,1% errors). From the analysis, the writer concludes that certain students have not mastered two tenses: Simple Present Tense (38% errors) and Simple Past Tense (52% errors). The occurrence of students’ errors in the Simple Present Tense and the Simple Past Tense might be caused by the students’ confusion because the two tenses are often used in the narrative writing and the regular use of the two tenses and there was a possibility of the students’ carelessness. The possible solutions that the writer provided are categorized in two types of errors which are form and function. To overcome the form error, the writer Magister Scientiae - ISSN: 0852-078X 45 Edisi No.23 - Maret 2008 suggested drill and exercises and to overcome function error, the writer suggested the Communicative Approach.